PENDAMPINGAN DAN PELATIHAN PENELITIAN TINDAKAN KELAS UNTUK GURU PAUD DAN SEKOLAH DASAR - Gigin Ginanjar; Vidya Ayuningtyas; Qois Abdul Qudus; Muhamad Sabiq Assyarifi; Yosi Lutfi Amelia; Sri Ratna Ayu (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Learning carried out by teachers needs to continue to improve its effectiveness in increasing students' understanding of the material being taught. Classroom Action Research (PTK) provides opportunities for teachers to improve student learning outcomes both from cognitive, affective and psychomotor aspects and at the same time becomes a form of professionalism. in managing the class. The aim of providing assistance and classroom action research training to teachers at Raudaltul Athfal (RA) and Madrasah Ibtidaiyah (MI) Fatimatul Jahroh is so that teachers have better classroom management skills in designing, conducting lessons and evaluating/reflecting on learning and writing the results of their good practices into an article which can be published. The mentoring and training method is carried out by providing material face-to-face (presentation) and then practicing directly creating articles from start to finish. The results of mentoring and training show that Raudaltul Athfal (RA) and Madrasah Ibtidaiyah (MI) Fatimatul Jahroh teachers can write the results of their classroom action research into articles that can be published to develop their competencies